2008
DOI: 10.1097/inf.0b013e318170b68b
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Central Venous Catheter Fungal Infection Using Liposomal Amphotericin-B Lock Therapy

Abstract: The current standard of care for a fungal central venous catheter infection in a pediatric patient usually requires removal without any other feasible options. Although removal may reduce the rate of Candida-associated complications, literature reviews question whether the outcomes of removal substantiate this being the standard of care. We report 6 cases of central venous catheter fungal infections treated with liposomal amphotericin-B lock therapy. These cases consisted of 4 patients, 2 of whom received recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 8 publications
1
26
0
3
Order By: Relevance
“…It should be noted that the miconazole concentrations used in our in vitro biofilm setup (0 to 2.4 mM) to observe the phenomenon of miconazole-tolerant persisters are higher than the commonly used therapeutic miconazole concentrations. However, such high concentrations are achievable during antifungal lock therapy (2,16). In the present study, we demonstrated an important role for superoxide dismutases in the occurrence of miconazole-tolerant persisters in C. albicans biofilms by using the Cu,Zn-Sod inhibitor N,NЈ-diethyldithiocarbamate (DDC).…”
Section: Discussionmentioning
confidence: 84%
“…It should be noted that the miconazole concentrations used in our in vitro biofilm setup (0 to 2.4 mM) to observe the phenomenon of miconazole-tolerant persisters are higher than the commonly used therapeutic miconazole concentrations. However, such high concentrations are achievable during antifungal lock therapy (2,16). In the present study, we demonstrated an important role for superoxide dismutases in the occurrence of miconazole-tolerant persisters in C. albicans biofilms by using the Cu,Zn-Sod inhibitor N,NЈ-diethyldithiocarbamate (DDC).…”
Section: Discussionmentioning
confidence: 84%
“…Most studies (5/7) reported 70 called for an RCT of CVC removal compared with retention in patients with candidaemia to address these serious biases in observational studies. 71 We included seven retrospective cohort studies that reported the association between CVC removal and risk of death, complications or recurrent infection in children (see Table 11). [45][46][47][48][49][50][51] The studies involved different patient groups (four studies were confined to neonates) [47][48][49][50] and different types of bloodstream infection (five studies were restricted to specific organisms), 45,[47][48][49]51 making it difficult to assess consistency of results.…”
Section: Resultsmentioning
confidence: 99%
“…Dans les études de Ko, Oncu et Shuford [26,27,29] [21] ont ainsi traité des infections sur cathéter à C. albicans [21], C. glabrata [21,31], C. parapsilosis [20,21] ou C. guillermondii [21], par des verrous utilisant l'amphotéricine B (déoxycholate ou liposomale) à des concentrations comprises entre 2,7 et 5 g/l en association à un traitement systémique par le fluconazole [31] ou l'amphotéricine B [20,21]. Selon Schinabeck et al [28], l'intérêt des traitements verrous est de lutter contre la résistance croissante des microorganismes se développant au sein d'un biofilm, d'éviter la toxicité des molécules utilisées dans le traitement systémique et ainsi de s'affranchir des dosages plasmatiques de ces molécules et, finalement, d'éviter la dissémination des microorganismes en verrouillant le cathéter.…”
Section: Verrous Fongiques : Modèles Et Efficacitéunclassified